Is laparoendoscopic single-site surgery (LESS) retroperitoneal hysterectomy feasible?: Surgical outcomes of the initial 27 cases - Tae-Hyun Kim; Tae-Joong Kim; Ha-Na Yoo; Yoo-Young Lee; Chel Hun Choi; Jeong-Won Lee; Duk-Soo Bae; Byoung-Gie Kim (Elsevier, 2015)
Objectives: The aim of the present study was to determine the feasibility of retroperitoneal hysterectomy by laparoendoscopic single-site surgery (LESS) and to suggest technical tips. Materials and methods: This study is a prospective single-center study. One surgeon trained in minimally invasive surgery performed LESS retroperitoneal hysterectomy on 27 consecutive patients with symptomatic uterine myomas or adenomyosis between September 2012 and February 2013. LESS retroperitoneal hysterectomy requires an additional eight steps including development of the retroperitoneal space, dissection of the ureter, and ligation of the uterine artery where it originates from the internal iliac artery. Results: LESS retroperitoneal hysterectomies were successfully performed in 23 (85.2%) patients. Of the four failed cases, three failed to develop the retroperitoneal space because of laterally located large myomas. Another patient with severe pelvic adhesion was converted to multiport laparoscopic vaginal hysterectomy. Total operative and bilateral uterine ligation time by the retroperitoneal approach was 84 (67.0-95.6) minutes and 16 (12-22) minutes, respectively. The median estimated blood loss was 150 (100-350) mL. One patient required postoperative transfusion. No other operative complications including ureteric injury were observed during the hospital stay or the 3-month follow-up period after discharge. Conclusion: LESS retroperitoneal hysterectomy is feasible and can be a good option.